KADAR KOLESTEROL DAGING AYAM BROILER SETELAH PEMBERIAN TEH KOMBUCHA - Tana, Silvana; Djaelani, Muhammad Anwar (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2015)
The purpose of this experiment was produce broiler chickens meat which less of cholesterol. This research used the CP 707 broiler strains of 20 broiler chickens aged a week, with treatment kombucha tea that has been fermented for 12 days at the temperature of 25oC. The research design used a completely randomized with 4 treatment (for 4 weeks) and 5 replications, namely: P0 = control, without of kombucha tea, P1 = water + 10% kombucha tea, P2 = water + 20% kombucha tea, P3 = water + 40% kombucha tea. Parameters measured were cholesterol levels, body weight and drink consumption. Data were analyzed with ANOVA followed by Duncan test at 95% confidence level were performed using SPSS version 10,0. The results showed that administration of kombucha tea can reduced the cholesterol meat levels significantly for broiler chickens.Â Key words: broiler chickens, kobucha tea, cholesterol